Effect of milk intake and method of weaning on calf performance and stress in an early-weaning program - P. Flynn; P.G. Reddy; J.L. Morrill; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 1986)
Feeding milk at 8% of birthweight and gradual weaning resulted in the most consistent increases in weekly weight gain, highest overall weight gain, and greatest increases in dry feed consumption during an 8-wk trial compared to feeding milk at 8% and abrupt weaning, at 10% and gradual weaning, or at 10% and abrupt weaning. By 8 wk, the 8% gradually-weaned calves also had higher levels of serum protein and lower levels of urea nitrogen in blood than calves in other treatment groups. Therefore, the 8% gradual-weaning program was determined to be the most appropriate for early weaning of dairy calves.; Dairy Day, 1986, Kansas State University, Manhattan, KS, 1986;
Keywords: Kansas Agricultural Experiment Station contribution; no. 87-88-S; Report of progress (Kansas Agricultural Experiment Station); 506; Dairy; Milk intake; Calf performance; Stress; Weaning